ENDOCROWN RESTORATION OF THE ENDODONTICALLY TREATED TEETH BY USING CAD/CAM: CASE SERIES - Begüm Ünlü Kurşun; Ender Akan (Ankara University, 2022)
Aim: As a result of large coronal destruction in endodontically treated teeth, significant losses occur in the dentin tissue around the pulp and the need for prosthetic treatment occurs. In this case series, endocrown applications produced in a single session with CAD/CAM system are presented as an alternative to crown restoration traditionally applied to premolar and molar teeth with excessive crown destruction. Case Series: In first case, 38-years-old male patient number 25, 46-years-old female patient number 36 in our second case, 21-years-old female patient number 46 in our third case, 26-years-old male patient number 46 in our fourth case, and in the last case 52-years-old male patient tooth number 15 has been applied to root canal treatment. As a result of the clinical and radiological examinations of the patients, it was observed that there were no systemic diseases. Endocrown restoration was considered appropriate and recommended to patients with less dentin tissue. Firstly, teeth are prepared for endocrown restoration. Afterwards, the impressions were digitalized by scanning the jaws with an intraoral optical scanner (Cerec Omnicam, Dentsply Sirona, USA). The restorations were designed with the help of the CEREC 4.3 software (Dentsply Sirona, USA) and the milling process was carried out using the feldspathic ceramic block (Vita Mark II, Vita Zahnfabrik, Germany) in the same session by CEREC inLab MC XL (Dentsply Sirona, USA). Later, the restorations were glazed and cemented with dual polymerized resin cement (RelyX Ultimate, 3M ESPE, USA). Conclusion: Endocrown restorations are a minimally invasive, conservative treatment approach that provides mechanical adhesion to the pulp chamber and cavity walls with adhesive resin cement and allows the preservation of the remaining tooth structure. For this reason, it is a treatment option that can be preferred instead of post-core and crown application in teeth with root canal treatment.